Anxiety Disorders and Quality of Life Among Patients with Intracranial Tumour and Other Brain Disorders in a Malaysian Hospital - Das, Priscilla; Nyi Naing, Nyi; Wan Arfah, Nadia; Noorjan, KON; Cheng Kueh, Yee; Rasalingam, Kantha (International Journal of Engineering and Technology, 2018)
The main objective of this study is to access the prevalence of anxiety disorders and its relationship with quality of life factors among intracranial tumour and other brain disorders in a Malaysian hospital. Methods: a cross-sectional research design was utilized in the study.Â  The research was conducted at the Kuala Lumpur Hospital, a tertiary referral center for brain cancer cases. Mini International Neuropsychiatric Interview (MINI) was used to access anxiety disorders and European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQC30) questionnaire for quality of life among the patients. Results: A total of 100 intracranial tumour and other brain disorders patients were included in the study. The prevalence of anxiety disorders in our study sample ranged from 3% to 31%. Overall, compared to patients without anxiety disorders, neurological disorders with anxiety disorders reported impaired quality of life in terms of physical functioning, emotional functioning, role functioning, social functioning fatigue, pain, insomnia, appetite loss, diarrhea, nausea and vomiting and global health status. The conclusions of this study support the fact that, like other cancer patients, intracranial tumour and other brain disorders patients are vulnerable in progressing anxiety disorders that could affect their overall quality of life.Â Â
Keywords: Anxiety; Quality of life; Brain tumour & Brain disorder.